Tinjauan Teori Al-Afuww terhadap Produk Makanan Kaki Lima yang Belum Tersertifikasi Halal - Muhamad Naufal Al Dzikri; Panji Adam Agus Putra; Neng Dewi Himayasari (Bandung Conference Series: Sharia Economic Law, 2023)
Abstract. Bandung is a city that is famous for its culinary tourism, both restaurants, cafes, and street food for all types of food and drinks are in the city of Bandung. In principle, in accordance with Law No. 33 of 2014 concerning Guarantees for Halal Products, all entrepreneurs or traders, be it those who sell food or beverage products, must guarantee the halalness of their products through halal certification. This is based on Article 4 of Law no. 33 of 2014 concerning Guarantee of Halal. but in reality there are still many street vendors (PKL) who do not have halal certification for the products they sell. This of course raises concerns for consumers, especially those who embrace Islam, about the dangers of contamination of haram substances in the products they consume. Based on this, the researcher is interested in researching "Al-Afuww Theory Review of Street Food Products That Have Not Been Halal Certified". This study uses qualitative methods, with a normative-empirical approach. Sources of data obtained for this study were obtained from interviews with street vendors as well as documentation on laws and the theory of Al-Afuww which is based on the Al-Quran and Hadith. The results of this study indicate that the reason that street vendors have not registered Halal Certification products is due to the lack of information they receive regarding registration of Halal certification. As well as with the noble nature of "Al-Afw" which belongs to Allah SWT, we can without worrying about consuming street food that is not yet halal certified due to limited ability and knowledge in terms of examining these products and Allah SWT has indirectly forgiven our mistakes or oversights regarding that matter. Abstrak. Bandung merupakan kota yang terkenal dengan wisata kulinernya, baik restoran, café, ada di kota Bandung. Pada prinsipnya sesuai dengan UU No 33 Tahun 2014 Tentang Jaminan Produk Halal, semua pengusaha atau pedagang baik itu yang menjual produk makanan maupun minuman harus sudah menjamin kehalalan produknya melalui sertifikasi halal. Namun pada kenyataannya dilapangan masih banyak para Pedagang Kaki Lima (PKL) yang masih belum memiliki sertifikasi halal pada produk yang dijualnya. Hal ini tentunya menimbulkan kekhawatiran bagi para konsumen khususnya yang memeluk Agama Islam akan bahaya dari pencemaran zat-zat haram pada produk yang dikonsumsinya. Berdasarkan hal tersebut maka peneliti tertarik untuk meneliti tentang “Tinjauan Teori Al-Afuww Terhadap Produk Makanan Kaki Lima Yang Belum Tersertifikasi Halal”. Penelitian ini menggunakan metode kualitatif, dengan pendekatan normative-empiris. Sumber data yang diperoleh untuk penelitian ini didapat dari hasil wawancara kepada Pedagang Kaki Lima dan juga Dokumentasi terhadap Undang-Undang dan Juga Teori Al-Afuww yang berlandaskan kepada Al-Quran dan Hadis. Hasil dari penelitian ini menunjukan bahwa Alasan para Pedagang Kaki Lima belum mendaftarkan produk Sertifikasi Halal karena kurangnya informasi yang mereka dapatkan terkait pendaftaran sertifikasi halal. Serta dengan adanya sifat mulia “Al-Afw” yang dimiliki Allah SWT, kita bisa tanpa khawatir mengkonsumsi makanan kaki lima yang belum bersertifikasi halal karena keterbatasan kemampuan maupun pengetahuan dalam hal menelaah produk tersebut dan Allah SWT secara tidak langsung telah memaafkan kesalahan ataupun kehilafan kita terkait hal tersebut.